Swallowing function, body image and uncertainty in illness after reconstruction in oral cancer survivors - Chen-Chan Kuo; Shiu-Yu C. Katie Lee; Chun-Ta Liao (Oral Oncology Reports)
Background: Swallowing and body image are the main concerns after reconstruction for oral cancer. Perceiving uncertainty or an unpredictable future is a significant psychosocial stressor in cancer survivors. This study aimed to explore swallowing function, body image, and uncertainty after the reconstruction for oral cancer, and to examine their associations. Methods: A consecutive sample of 155 oral cancer adults (147 males and 8 females), with or without adjuvants, and surviving 3–30 months after primary microvascular free flaps, were included. The main outcomes were assessed by the Body Image Scale, EORTC QLQ-HN 35, and Mishel's Uncertainty in Illness Scale. Results: Participants reported moderate disturbance in appearance, body as a whole, and sexual attraction, and a moderate-to-low level of EORTC swallowing, speech, and social problems. Less than 20 % have pursued cosmetic surgeries after reconstruction. After adjusting for demographic and clinical factors, poor body image (β = .318), poor speech (β = .198), lower household incomes (β = -.153), and farmers v.s. counterparts were more likely to have higher uncertainty in illness (Adj.R2 = .347). Conclusions: Along with body image disturbance and swallowing problems, financial burden or work-related stress are significant risk factors for higher uncertainty in illness. Providing supportive care to cope with body image disturbances, swallowing and speech problems, and to improve work or financial status are warranted to help oral cancer survivors to cope with uncertainty in illness after free flaps.